The necessity for human solidarity in Arthur Miller’s All My Sons - Mowaad, Mostafa Saber Abdel-Hamid (Advances in Social Sciences Research Journal, 2020)
Arthur Miller’s All My Sons depicts the human tendency of self-deception, betrayal and guilt which leads to the deterioration and the collapse of human values. The intensity of these elements may vary but they run through all of his plays. In All My Sons, Joe, a selfish businessman, in order to save his business from ruin, supplies defective cylinder heads to the American Air Force which results in the death of 21 fighter plane pilots. Joe atones for his crime by committing suicide. According to Miller, the American Dream creates false hopes that prevent people from being proud of what they have accomplished to make their lives better than they would be elsewhere, and eventually fail at achieving anything. Guilt is fundamentally a prosocial behavior because it strengthens interpersonal relationships. It is a kind of regretful, remorseful, painful, and aversive feeling aroused by one’s own actions or inactions. Guilt is different from regret in that guilt is more related to interpersonal harm whereas regret is more related to intrapersonal harm. Guilt is usually related to and is operationalized as the acceptance of responsibility for harm. Guilt has long been related to prosocial behavior. People tend to use altruistic means when under the stress of guilt.1